PENERAPAN MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT UNTUK MENINGKATKAN MINAT BELAJAR IPA SISWA DI MTS NU BATAHAN - Okta Viana; Eni Sumanti Nasution; Sri Utami Kholilla Mora Siregar (Universitas Gara Nusantara Padangsidimpuan, 2025)
This study investigates the effectiveness of the Teams Games Tournament (TGT) model in enhancing students' interest and learning outcomes in science subjects at MTs NU Batahan. The research was conducted in two cycles, utilizing a quantitative approach for data collection through observations, questionnaires, and assessments. The findings revealed a significant increase in student engagement, rising from 75% in Cycle 1 to 90% in Cycle 2. Additionally, positive feedback from students improved from 70% to 90%. Observations indicated enhanced interaction among students and notable improvements in their discussion skills. The implementation of the TGT model not only fostered a collaborative learning environment but also encouraged students to take greater responsibility for their learning. This research provides evidence supporting the effectiveness of cooperative learning strategies, particularly the TGT model, in creating a more active and engaging classroom atmosphere. The results highlight the importance of innovative teaching methods in improving both students' motivation and academic performance in science education.